Failures and Reliability in Hawts Operating in Mountainous Areas, Open Sea and in Harsch Climate Sites - Maria De Pratti Giovanni (EDP Sciences, 2021)
Recently, offshore wind plants, as Horn’s Riv one, have reached a remarkable interest and development. In these sites, HAWT’s blades experiment corrosion, erosion and fouling and, at higher latitudes, icing conditions too, as in mountainous areas and in harsch climate sites. The operative conditions may influence the machine damages and they may occur as consequence of erosion, corrosion, fouling, icing, exfoliation caused by the above mentioned environmental conditions. The paper reports about data collection about failures occurred to HAWTS operating in offshore, mountainous and harsch climate sites in last ten years. Particularly, the damage occurred to blades, gears and bearings have been examined and the consequences analysed. The occurred failures are examined and the reliability of WTGs is assessed by appropriate models and analysis. The results are com pared to literature data and they may be very useful in programmable maintenance and in predictable one. Reliability analysis may be also useful to increase energy production.